Evaluation of Genetic Diversity Uses SSR and ISSR Markers on Date Palm Cultivars that Propagated through tissue culture and vegetative propagation. - Al-hamza A.M. Al-Salim; Aqeel A. Suhaim; Osama N. Jaffer (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
The spread of tissue culture date palm cultivation in Iraq in recent years has played an important role in reviving date palm cultivation. To study the genetic diversity of tissue culture date palm and match them with some Iraqi cultivars molecular markers for (SSR) and (ISSR) were used.The current study was conducted on ten date palm cultivars (five tissue-cultured cultivars) which are (Barhi, Saqai, Khalas, Zamli, and Maghrebi), and five vegetatively propagated cultivars which are (Barhi, Hasawi, Breem, Dieri, and Shukr). Five primers were used for ISSR technique (ubc815, ubc842, ubc858, 834, 825) and five primers for the SSR technique (SSR009, SSR016, 1036, 270, GI298295793). The results were analyzed using Jaccard's coefficient, and a dendrogram using the UPGMA method of NTSYS-PC program. ISSR results showed that 28 polymorphic bands and 18 monomorphic bands. The efficiency of the primers ranged between (14.2-25) %, polymorphism (57.1-100) . Except for primer 834, its indices decreased to the lowest level and reached (20%, 17.85 %) respectively. SSR results showed 35 polymorphic bands and 34 monomorphic bands. The efficiency of the primers ranged between (14.28-100) %, polymorphism (80-100) % . Except for primer GI298295793, its efficiency decreased to 8.57% . It is concluded from the study that the cultivars propagated through plant tissue culture did not show significant genetic variation among themselves, Therefore, this method can be adopted for productive propagation for date palms.